Impact of Hemlock Woolly Adelgid (Hemiptera: Adelgidae) Infestation on the Jasmonic Acid-Elicited Defenses of Tsuga canadensis (Pinales: Pinaceae). Issue 5 (16th September 2020) - Rigsby, Chad M; Kinahan, Ian G; May, Amelia; Kostka, Amy; Houseman, Nick; Savage, Suzanne K; Whitney, Elizabeth R; Preisser, Evan L
Abstract: Hemlock woolly adelgid is an invasive piercing-sucking insect in eastern North America, which upon infestation of its main host, eastern hemlock ('hemlock'), improves attraction and performance of folivorous insects on hemlock. This increased performance may be mediated by hemlock woolly adelgid feeding causing antagonism between the the jasmonic acid and other hormone pathways. In a common garden experiments using hemlock woolly adelgid infestation and induction with methyl jasmonate (MeJA) and measures of secondary metabolite contents and defense-associated enzyme activities, we explored the impact of hemlock woolly adelgid feeding on the local and systemic induction of jasmonic acid (JA)-elicited defenses. We found that in local tissue hemlock woolly adelgid or MeJA exposure resulted in unique induced phenotypes, whereas the combined treatment resulted in an induced phenotype that was a mixture of the two individual treatments. We also found that if the plant was infested with hemlock woolly adelgid, the systemic response of the plant was dominated by hemlock woolly adelgid, regardless of whether MeJA was applied. Interestingly, in the absence of hemlock woolly adelgid, hemlock plants had a very weak systemic response to MeJA. We conclude that hemlock woolly adelgid infestation prevents systemic induction of JA-elicited defenses. Taken together, compromised local JA-elicited defenses combined with weak systemic induction could be major contributors to increased folivore performance on hemlock woolly adelgid-infested hemlock.